Conceptual study of hydrogen powered wheelbarrow using fuel cell - Muhamad Afiq, Saukit (2013)
The design, fabrication, and testing of a prototype of a wheelbarrow powered by a fuel cell is reported. Usually wheelbarrow does not have motor and need more energy to use. An conceptual study on this project is the idea on how the project can be done properly. The compact systems consist of hydrogen generator, fuel cell, motor and the wheelbarrow. The project focused on the conceptual study of system in the fuel cell that can be powered wheelbarrow. This research define the power of electric motor that need to move 80 kg load is 0.082 kW for the minimum and 0.22 kW for the maximum power with velocity 2.78 m/s. Hydrogen generator cost also has been define, hydrogen cost for this project is RM 39.90. Number of molar and molar mass of hydrogen has been calculated for move 80kg load. The number of molar hydrogen is 0.149 gmol/hr, and the number of molar mass of hydrogen is 3.003 x 〖10〗^(-4) (kgH_2)/(hr.A)